How I treat Parkinson's disease - Egberto Reis Barbosa; João Carlos Papaterra Limongi; Hsin Fen Chien; Pedro Melo Barbosa; Marcela Reuter Carréra Torres (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Parkinson’s disease (PD) is a complex neurodegenerative condition. Treatment strategies through all stages of disease progression could affect quality of life and influence the development of future complications, making it crucial for the clinician to be on top of the literature. Objective: This paper reviews the current treatment of PD, from early to advanced stages. Methods: A literature review was conducted focusing on the treatment of PD, in the different stages of progression. Results: Every individual with a new diagnosis of PD should be encouraged to start exercising regularly. In the early stage, treatment should focus on using the lowest dose of levodopa or combination therapy that provides maximum functional capacity, and does not increase the risk of complications, such as peak dose dyskinesias and impulse control disorders. At the moderate and advanced stages, motor fluctuations and complications of treatment dominate the picture, making quality of life one important issue. Rehabilitation programs can improve motor symptoms and should be offered to all patients at any stage of disease progression. Conclusion: Many factors need to be considered when deciding on the best treatment strategy for PD, such as disease progression, presence of risk factors for motor and behavioral complications, potential side effects from dopaminergic therapy and phenotypical variabilities. Treatment should focus on functional capacity and quality of life throughout the whole disease course.